A collective navigation hypothesis for homeward migration in anadromous salmonids. Issue 2 (24th June 2014) - Berdahl, Andrew; Westley, Peter A H; Levin, Simon A; Couzin, Iain D; Quinn, Thomas P
Abstract: Anadromous salmon (genera Oncorhynchus and Salmo ) spend much of their lives feeding in productive northern oceans and then return home to natal sites for reproduction with remarkable accuracy. The mechanisms used for navigation by individuals during migrations are thought to include geomagnetic, celestial and olfactory cues, but rarely are social interactions between individuals considered. Mounting evidence from other taxa indicates that individuals in larger groups can better sense and respond to environmental cues, thus potentially increasing their ability to navigate. Here, we propose that salmon might similarly benefit from collective navigation on their homeward journey. To explore this, we compiled data from multiple studies and found strong evidence that rates of successful homing increase with population abundance, consistent with collective navigation. We then discuss how collective navigation could benefit salmon during each stage of their seaward and homeward migrations, and complement this with a review of salmon sociality. Next, we analyse historic high‐seas catch records and provide new insight into schooling structure of salmon in the marine environment. We argue that collective navigation likely represents a presently under‐appreciated mechanism enhancing the navigational ability of salmon as well as other migratory species, and outline critical tests of our hypothesis.